Assessment of a Nutritional Rehabilitation Model in Two Modern Broilers and Their Jungle Fowl Ancestor: A Model for Better Understanding Childhood Undernutrition - Baxter, Mikayla F. A.; Latorre, Juan D.; Koltes, Dawn A.; Dridi, Sami; Greene, Elizabeth S.; Bickler, Stephen W.; Kim, Jae H.; Merino-Guzman, Ruben; Hernandez-Velasco, Xochitl; Anthony, Nicholas B.; Bottje, Walter G.; Hargis, Billy M.; et al. (Frontiers in Nutrition, 2018)
This article is the first in a series of manuscripts to evaluate nutritional rehabilitation in chickens as a model to study interventions in children malnutrition. Inclusion of rye in poultry diets induces a nutritional deficit that leads to increased bacterial translocation, intestinal viscosity, and decreased bone mineralization. However, it is unclear the effect of diet on developmental stage or genetic strain. Therefore, the objective was to determine the effects of a rye diet during either the early or late phase of development on performance, bone mineralization and intestinal morphology across 3 diverse genetic backgrounds. Modern 2015 (Cobb 500) broiler chicken, 1995 Cobb broiler chicken, and the Giant Jungle Fowl were randomly allocated into four different dietary treatments. Dietary treatments were 1) a control corn-based diet throughout the trial (corn-corn); 2) an early phase malnutrition diet where chicks received a rye-based diet for 10 days, and then switched to the control diet (rye-corn); 3) a malnutrition rye-diet that was fed throughout the trial (rye-rye); and 4) a late phase malnutrition diet where chicks received the control diet for 10 days, and then switched to the rye diet for the last phase (corn-rye). At ten days of age, chicks were weighed and diets were switched in groups 2 and 4. At day 20 of age, all chickens were weighed and euthanized to collect bone and intestinal samples. Body weight, weight gain and bone mineralization were different across diet, genetic line, age and all 2 and 3-way interactions (P<0.05). Overall, Jungle fowl were the most tolerant to a rye based diet, and both the modern and 1995 broilers were significantly affected by the high rye based diet. However the 1995 broilers consuming the rye based diet appeared to experience more permeant effects when compared to the modern broiler. The results of the present study suggest that chickens have a great potential as a nutritional rehabilitation model in human trials. The 1995 broilers line was an intermediate genetic line between the fast growing modern line and the non-selected Jungle Fowl line, suggesting it would be the most appropriate model to study for future studies.